Essential Oil From Knema Elegans Warb: Chemical Composition, Antioxidant and Anti-acetylcholinesterase Activities - THIN, Dau B.; HOA, Truong T. V.; THINH, Bui B. (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Knema elegans Warb. is an evergreen tree belonging to the Myristicaceae family, primarily native to Southeast Asia. This study examined the chemical composition and assessed the antioxidant and anti-acetylcholinesterase properties of the essential oil from the leaves of K. elegans in Vietnam. Gas chromatography/mass spectrometry analysis revealed the main compounds in the essential oil, including bicyclogermacrene (23.8%), germacrene D (17.1%), β-caryophyllene (15.4%), δ-cadinene (8.2%), and α-cadinol (7.9%). Antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) methods, with half-maximum inhibitory concentration (IC50) values of 93.11 ± 1.95 µg/mL and 114.95 ± 2.41 µg/mL, respectively, indicating moderate antioxidant potential. Additionally, the essential oil exhibited significant anti-acetylcholinesterase effects, with an IC50 value of 87.44 ± 2.52 µg/mL. These findings highlight the biological significance of K. elegans essential oil and suggest avenues for further investigation, particularly in elucidating its mechanisms of action in antioxidant and anti-acetylcholinesterase activities. Notably, this research represents the first comprehensive exploration of the chemical composition, antioxidant activity, and acetylcholinesterase inhibition effects of K. elegans essential oil from its leaves.